Chemically surface-engineered polydimethylsiloxane layer via plasma treatment for advancing textile-based triboelectric nanogenerators. (March 2019) - Lee, Choonghyun; Yang, Seungmo; Choi, Dasong; Kim, Woojong; Kim, Jaeho; Hong, Jinpyo
Abstract: Energy-harvesting devices as basic components of independent power sources are highly promising for use in modern portable smart electronics. In this regard, the use of conductive textile substrates in triboelectric nanogenerators (T-TENG) that convert sustainable mechanical energy to electricity has emerged as an alternative option for efficient power generation. Here, we address the enhancement of the electrical performances of T-TENGs by employing chemically surface interface-engineered polydimethylsiloxane (SIE-PDMS) layers as coatings on highly conductive Ni-Cu textile substrates. Manipulation of the PDMS surface is a major approach in this work, where in-situ two-step reactive-ion plasma treatments were conducted with sequential Ar and CF4 + O2 plasmas. Structural observations identified the appearance of F on the SIE-PDMS after suitable CF4 +O2 plasma treatment, thus yielding enhanced output generation by the T-TENG through efficient surface charging ability, which was attributed to the large electronegativity of F. We anticipate that this simple fabrication approach may facilitate the development of highly wearable self-powered devices. Graphical abstract: The enhanced performance of T-TENGs was achieved by employing chemically surface interface-engineered polydimethylsiloxane (SIE-PDMS) layers coated on highly conductive Ni-Cu textile substrates. Manipulation of in-situ two-step reactive-ion plasma treatments was one of key factors through the assistance of an initial Ar plasma treatment. fx1 Highlights: A flexible and conductive textile-based triboelectric nanogenerator was achieved for efficient power generation. Enhanced electrical performance resulted from the appearance of F on the SIE-PDMS after in-situ two step plasma treatment. F element on the SIE-PDMS provided efficient surface charging ability due to the large electronegativity of F.